Evaluation of the Effectiveness of Welfare Programs in Academic Environments: Quantitative Study and Data Analysis - Musmulyadin, Musmulyadin; Jun, Wang; Mei, Chen (Yayasan Adra Karima Hubbi, 2025)
The effectiveness of welfare programs in academic environments plays a crucial role in enhancing faculty performance, student satisfaction, and overall institutional development. Despite their significance, limited studies comprehensively analyze the impact of such programs using robust quantitative methods. This study aims to evaluate the effectiveness of welfare programs implemented in academic settings, focusing on their influence on academic stakeholders' well-being and productivity. A quantitative approach was employed, involving a structured survey distributed to 500 faculty members and administrative staff from 10 universities across different regions. Data analysis was conducted using descriptive statistics, regression modeling, and structural equation modeling to identify key factors contributing to program success. The findings revealed that well-structured welfare programs significantly improve job satisfaction, reduce burnout, and enhance institutional loyalty. Factors such as accessibility, inclusivity, and alignment with stakeholders' needs emerged as critical determinants of program effectiveness. Programs promoting work-life balance and professional development showed the highest impact on participants' well-being and performance. In conclusion, this study underscores the necessity for tailored welfare programs that address the specific needs of academic environments. Future research should explore longitudinal impacts and incorporate diverse cultural contexts to broaden understanding.